PSVI-29 Late-Breaking: Exposure to 1.8 mM choline chloride does not impact development to the blastocyst stage or pregnancy rate after transfer for embryos produced in vitro. (8th October 2021) - Haimon, McKenzie L; Estrada-Cortés, Eliab; Amaral, Thiago F; Jeensuk, Surawich; Sosa, Froylan; Bittar, João; Block, Jeremy; Heredia, Daniella C; Gonella-Diaza, Angela Maria M; Di Lorenzo, Nicolas; Hansen, Peter J
Abstract: Choline is a nutrient that plays a role as a precursor for the neurotransmitter acetylcholine, the membrane phospholipid phosphatidylcholine, and the methyl donor betaine. Embryos produced in vitro are usually cultured without an exogenous choline source. We hypothesized that exposure to 1.8 mM choline chloride would increase percent of embryos becoming blastocysts in culture and pregnancy rate after transfer of embryos into recipients. A total of 39 Brahman and Senepol donors were used to produce embryos for transfer into recipient crossbred females. Donors were assigned to have their embryos cultured in either 1.8 mM choline chloride or, as a control, 1.8 mM extra NaCl. The percent of oocytes cleaved were measured 3 days after insemination and percent blastocyst at day 7.5. Embryos were transferred into recipient cows and pregnancy was diagnosed at 28–31 days of gestation and then confirmed at 50–56 days. Data were analyzed using PROC GLIMMIX in SAS. Treatment did not affect cleavage rate (67.3 + 1.6 vs 68.6 + 1.6% for choline vs control; P = .0.5632) or percent of cleaved embryos becoming blastocysts (17.6 + 1.3 vs 18.1 + 1.3%; P = 0.5355). Similarly, there was no effect of treatment on pregnancy days 28–31 [42.5% (48/113 cows) vs 47.3% (54/114 cows) for choline vs control; P = 0.4339] or at days 50–56 [39.1% (36/92) vs 38.5% (32/83); P = 0.5348]. In summary, 1.8 mM choline chloride does not impact embryo development to the blastocyst stage or pregnancy establishment. Further investigation is needed to evaluate the phenotype of the subsequent calves to determine whether early exposure to choline has consequences for postnatal function. Support: USDA-NIFA 2020-67015-30821.